Cell-specific loss of SNAP25 from cortical projection neurons allows normal development but causes subsequent neurodegeneration - Hoerder-Suabedissen, A; Korrell, KV; Hayashi, S; Jeans, A; Ramirez, DMO; Grant, E; Christian, HC; Kavalali, ET; Wilson, MC; Molnár, Z (Oxford University Press, 2018)
Synaptosomal associated protein 25 kDa (SNAP25) is an essential component of the SNARE complex regulating synaptic vesicle fusion. SNAP25 deficiency has been implicated in a variety of cognitive disorders. We ablated SNAP25 from selected neuronal populations by generating a transgenic mouse (B6-Snap25tm3mcw (Snap25-flox)) with LoxP sites flanking exon5a/ 5b. In the presence of Cre-recombinase, Snap25-flox is recombined to a truncated transcript. Evoked synaptic vesicle release is severely reduced in Snap25 conditional knockout (cKO) neurons as shown by live cell imaging of synaptic vesicle fusion and whole cell patch clamp recordings in cultured hippocampal neurons. We studied Snap25 cKO in subsets of cortical projection neurons in vivo (L5—Rbp4-Cre; L6—Ntsr1-Cre; L6b—Drd1a-Cre). cKO neurons develop normal axonal projections, but axons are not maintained appropriately, showing signs of swelling, fragmentation and eventually complete absence. Onset and progression of degeneration are dependent on the neuron type, with L5 cells showing the earliest and most severe axonal loss. Ultrastructural examination revealed that cKO neurites contain autophagosome/lysosome-like structures. Markers of inflammation such as Iba1 and lipofuscin are increased only in adult cKO cortex. Snap25 cKO can provide a model to study genetic interactions with environmental influences in several disorders.